Gene-specific transcriptional mechanisms at the histone gene cluster revealed by single-cell imaging. - Guglielmi, B.; La Rochelle, N.; Tjian, R. (Molecular Cell, 2013)
To bridge the gap between in vivo and in vitro molecular mechanisms, we dissected the transcriptional control of the endogenous histone gene cluster (His-C) by single-cell imaging. A combination of quantitative immunofluorescence, RNA FISH, and FRAP measurements revealed atypical promoter recognition complexes and differential transcription kinetics directing histone H1 versus core histone gene expression. While H1 is transcribed throughout S phase, core histones are only transcribed in a short pulse during early S phase. Surprisingly, no TFIIB or TFIID was detectable or functionally required at the initiation complexes of these promoters. Instead, a highly stable, preloaded TBP/TFIIA "pioneer" complex primes the rapid initiation of His-C transcription during early S phase. These results provide mechanistic insights for the role of gene-specific core promoter factors and implications for cell cycle-regulated gene expression.